Strengthening environmentally based accounting to improve the sustainability and economic value of waste banks - Murdhaningsih Murdhaningsih; Agustina Riyanti; Rahmiyatus Syukra (PT WIM Solusi Prima, 2026)
Environmental accounting is a strategic approach to supporting sustainable community-based waste management. Waste banks play a crucial role not only in reducing the volume of waste entering landfills (TPA), but also in creating economic value through waste sorting and recycling. However, most waste banks still face challenges in financial recording and management due to a limited understanding of accounting principles, particularly those integrated with environmental aspects. This community service activity aims to improve the understanding and skills of the waste bank administrators of RW 04 Benda Baru, Pamulang, in implementing environmental accounting as a basis for transparent and accountable financial management. The implementation method includes initial observation to identify partner needs, training through lectures and practical training in preparing simple financial records, and activity evaluation to measure the level of participant understanding. The results of the activity indicate an increase in participant knowledge regarding environmental accounting concepts, particularly in identifying environmental costs and benefits and preparing simple financial reports relevant to waste bank activities. In addition, participants also demonstrated an increased awareness of the importance of transparency and accountability in financial management. This community service activity has implications for increasing the operational efficiency of the Waste Bank, strengthening financial governance, and supporting environmental conservation efforts and achieving the Sustainable Development Goals (SDGs).